Environmentally-friendly preparation of Sn(II)-BDC supported heteropolyacid as a stable and highly efficient catalyst for esterification reaction - Qiuyun Zhang; Xingyue Hong; Jiao Lei; Yanting Lei; Yigang Yang; Jingsong Cheng; Yulin Hu; Yutao Zhang (Journal of Saudi Chemical Society, 2024)
Facilitating energy resource deficiency and environmental contamination, this work focuses on sustainable biodiesel production through the esterification reactions of oleic acid (OA) with methanol. To address the reaction, a novel heterogeneous acid catalyst, 12-tungstophosphoric acid (TPA) immobilized on Sn-based MOFs (Sn(II)-BDC) was synthesized via a simple, green solvent, and easy-to-implement synthesis strategy for the first time, and applied effectively for esterification process of OA to produce biodiesel. The structure and composition of as-obtained catalyst have been verified using XRD, FTIR, N2 physisorption, SEM, EDX, TG, Py-FTIR, TPD-NH3, and XPS techniques. The obtained TPA/Sn(II)-BDC catalyst was found to be the best with 60 wt% of TPA loading, which resulted in an OA conversion of 91.7 % at optimized conditions of 0.15 g catalyst loading and methanol to OA molar ratio of 20:1 at temperature of 120 °C in 4 h, and the excellent performance arises from available pores structure, large amounts of acidic sites, good stability and the synergistic catalytic effect of TPA and Sn(II)-BDC. Furthermore, the composite catalyst reusability has been studied for five cycles, and it exhibits an acceptable conversion. This research provides a green and large-scale synthesis route for the sustainable production of biofuels by constructing heteropolyacids/Sn-based MOFs synergistic catalysts.